1987
DOI: 10.1016/0014-5793(87)81059-1
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a thiol‐activated T‐kininogenase from the rat submandibular gland

Abstract: T-kininogenase (T-kgnase) activity has been investigated in tissues of the rat and submandibular glands of the rat, mouse and guinea pig. Both rat and mouse submandibular homogenates showed high T-kgnase activity. The enzyme has been purified 360-fold from rat submandibular gland homogenate supematant fluid. The enzyme has an apparent molecular mass of 28 kDa and a pH optimum of 8.0 toward T-kininogen. It cleaved T-kininogen in catalytic quantities to release T-kinin (Ile-Ser-bradykinin) and small quantities o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

1989
1989
2000
2000

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…Another kinin, T-kinin (Ile-Serbradykinin), was described in rats (Okamoto and Greenbaum 1984). However, T-kinin is released from T-kininogen only by massive amounts of trypsin or by a T-kininogenase restricted to salivary glands (Adam et al 1986;Barlas et al 1987). In inflammatory exudates occurring in normal rats, the main kinin released from kininogens is bradykinin (Damas et al 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Another kinin, T-kinin (Ile-Serbradykinin), was described in rats (Okamoto and Greenbaum 1984). However, T-kinin is released from T-kininogen only by massive amounts of trypsin or by a T-kininogenase restricted to salivary glands (Adam et al 1986;Barlas et al 1987). In inflammatory exudates occurring in normal rats, the main kinin released from kininogens is bradykinin (Damas et al 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that a large number of soluble proteases from submaxillary gland have been studied [1][2][3][4][5][6][7], information on intracellular membrane proteases from this tissue is scarce [8][9][10]. These enzymes are of interest as they are known to be involved in several cellular functions.…”
Section: Introductionmentioning
confidence: 99%
“…Several proteins of the kallikrein family have been demonstrated in the rat submandibular gland (SMG). These include tissue kallikrein (rKl) (Brandtzaeg et al, 1976), tonin (rK2) (Boucher et al, 1974), esterase B (rK7) (Khullar et al, 1986;Elmoujahed et al, 1990;Berg et al, 1992b), rK8, shown to be identical with P1 (Elmoujahed et al, 1990), rK9, formerly reported as prostatic protease (Winderickx et al, 1989), SEV (Yamaguchi et al, 1991) or KLP-S3 (Berg et al, 1992a), rKlO (Gutman et al, 1991), which is identical with antigen y (Berg et al, , 1991, and probably also proteinase B (Kato et al, 1987) and T-kininogenase (Barlas et al, 1987;Xiong et al, 1990).…”
Section: Introductionmentioning
confidence: 99%